Plasmodium falciparum hyperparasitaemia: use of exchange transfusion in seven patients and a review of the literature. - Looareesuwan, S; Phillips, R; Karbwang, J; White, N; Flegg, P; Warrell, D (1990)
During the last 15 years, at least 35 patients with severe falciparum malaria or babesiosis have recovered following treatment by exchange of up to 10 l of blood. In a patient treated in Manchester, a parasitaemia of 2.10 X 10(6) microliters (42 per cent) was virtually eliminated over eight hours by a 3.5 litre exchange blood transfusion. However, the equipment and amounts of compatible blood required for total exchange are rarely available in areas endemic for malaria and the risks of the procedure, including transfusion-related infections, are high. Partial exchange transfusion with one to two litres of blood carried out over two to seven hours, reduced Plasmodium falciparum parasitaemias of 0.33-1.48 X 10(6)/microliters (13-38 per cent) to 0.11-0.81 X 10(6) (4-17 per cent) in six Thai patients who were receiving intravenous quinine. The reduction in parasitaemia ranged from 0.13-0.67 X 10(6) microliters (9-12 per cent) within six hours. During the same period, parasitaemia in 13 patients with cerebral malaria treated with chemotherapy alone showed little reduction from initial levels of 0.20-1.74 X 10(6)/microliters (11-42 per cent). One of the patients who were treated with exchange transfusion died with intractable hypotension before the procedure could be completed and two others developed oliguric renal failure which was controlled by peritoneal dialysis. Partial exchange transfusion is a promising and practical alternative to total exchange where facilities are limited. It deserves further assessment in the rural tropics.